RMR Criteria Levels For Testing Metabolic Level Using Fitmate Pro For Youth Handball Players - Abedulsalam, Nada (Journal of Physical Education, 2016)
The aim of the research is to identify the RMR using (Fitmate Pro) for youth handball players as well as placing criteria for testing RMR metabolic level. The researcher used the descriptive method. The subjects were 74 youth handball players from five clubs of the season 2016. The tests were conducted in the physiology lab in the college of physical education and sport sciences for women. The test was applied from 2/1/2016 – 29/1/2016. The results were collected and treated using proper statistical methods using the SPSS. The researcher concluded that physiological apparatuses' results only are not enough for evaluating the athlete's condition unless standard levels for them. Standardizing the test led to the achievement of six standard levels for evaluating metabolic rate RMR for youth handball players using fitmate pro.